Atrial Structure and Function 5 Years After Successful Ablation for Persistent Atrial Fibrillation: An MRI Study. (5th June 2014) - COCHET, HUBERT; SCHERR, DANIEL; ZELLERHOFF, STEPHAN; SACHER, FREDERIC; DERVAL, NICOLAS; DENIS, ARNAUD; KNECHT, SEBASTIEN; KOMATSU, YUKI; MONTAUDON, MICHEL; LAURENT, FRANÇOIS; PIESKE, BURKERT M.; HOCINI, MÉLÈZE; et al.
Atrial Function After Persistent AF Ablation Introduction The atrial outcome after extensive ablation is unknown. We sought to quantify atrial structure and function years after successful ablation for persistent atrial fibrillation (PsAF). Methods and Results We studied after 80 ± 15 months 26 patients (54 ± 8 years, 1 woman) with PsAF successfully treated by ablation (2.2 ± 0.7 stepwise approach procedures, cumulative RF duration 126 ± 37 minutes). At follow‐up atrial scar burden and atrial outflows were quantified using delayed–enhanced and velocity‐encoded MRI, respectively. Cine imaging was used to quantify atrial conduit function (CF), active emptying fraction (AEF), expansion index (EI), and the inter‐appendage mechanical activation delay. Patients underwent exercise testing at baseline and follow‐up. LA and RA scar extent were 29 ± 6 and 4.3 ± 2.8%, respectively. LA and RA AEF were 10.0 ± 5.3 and 30 ± 8%. Mean inter‐appendage delay was 83 ± 47 ms [42–217]. Complete LAA isolation was found in 3 patients. A wave was absent in 9/26 patients. LA scar extent related to the number of procedures (R = 0.58, P = 0.002) and total RF duration (R = 0.56, P = 0.003). Among follow‐up characteristics, LA scar extent related to LAAEF (R = −0.73, P < 0.0001), LAEI (R = −0.64, P = 0.0003), A‐wave peak (R = −0.72, P < 0.0001), and inter‐appendage mechanical delay (R = 0.47, P = 0.02). At multivariable analysis, LA scar extent was independently related to LAAEF and LAEI. LAAEF and LA scar extent correlated with exercise capacity at follow‐up (R = 0.44, P = 0.02, and R = −0.40; P = 0.04). Conclusion LA contractility and compliance are markedly impaired years after successful PsAF ablation. LA dysfunction is closely related to scar burden.